Optical Coherence Tomography Evaluation of Carotid Artery Stenosis and Stenting in Patients With Previous Cervical Radiotherapy - Xu, Xiaohui; Huang, Feihong; Shi, Xuan; Liu, Rui; Han, Yunfei; Li, Min; Wang, Fang; Yang, Qingwen; Zhu, Wusheng; Ye, Ruidong; Liu, Xinfeng (Frontiers in Neuroscience, 2022)
Objectives Cervical radiotherapy can lead to accelerated carotid artery stenosis, increased incidence of stroke, and higher rate of in-stent restenosis in irradiated patients. Our objective was to reveal the morphological characteristics of radiation-induced carotid stenosis and the stent-vessel interactions in patients with previous cervical radiotherapy by optical coherence tomography. Materials and Methods Between November 2017 and March 2019, five patients with a history of cervical radiotherapy were diagnosed as severe carotid artery stenosis and underwent carotid artery stenting. Optical coherence tomography was conducted before and immediately after the carotid stent implantation. Two patients received optical coherence tomography evaluation of carotid stenting at 6-month or 13-month follow-up. Results The tumor types indicating cervical radiotherapy were nasopharyngeal carcinoma (n=3), cervical esophageal carcinoma (n=1), and cervical lymphoma (n=1). The median interval from the radiotherapy to the diagnosis of radiation-induced carotid stenosis was 8 years (range 4-36 years). Lesion characteristics of radiation-induced carotid stenosis detected included heterogeneous signal-rich tissue, dissection, and advanced atherosclerosis upon optical coherence tomography evaluation. Post-interventional optical coherence tomography revealed 18.2-57.1% tissue protrusion and 3.3-13.8% stent strut malapposition. Follow-up optical coherence tomography detected homogeneous signal-rich neointima and signal-poor regions around stent struts. In the patient with high rates of tissue protrusion and stent strut malapposition, the 6-month neointima burden reached 48.9% and microvessels were detected. Conclusions The morphological features of radiation-induced carotid stenosis were heterogeneous, including heterogeneous signal-rich tissue, dissection, and advanced atherosclerosis. Stenting was successful in all 5 patients with severe radiation-induced carotid stenosis. One patient, with high rates of tissue protrusion and stent strut malapposition immediately after stenting, received in-stent neointimal hyperplasia at 6-month follow-up.